A RP-HPLC Method for the Determination of Ketoconazole in Pharmaceutical Dosage Forms - Popovska, Olga; Kavrakovski, Zoran; Rafajlovska, Vesna (Current Pharmaceutical Analysis, 2017)
Background: Ketoconazole is an antifungal drug, available in different pharmaceutical dosage forms. The current published methods for the ketoconazole determination confirmed the primacy of the HPLC method, but high toxic solvents were used, also. Introduction: A new simple, precise, accurate, and cost-effective RP-HPLC method for the determination of ketoconazole in tablets, topical cream, and shampoo has been developed and validated. Method: The chromatographic separation was conducted on a LiChrospher®100 C-18 column (150 mm length x 4.6 mm i.d., 5 µm particle size) using a mixture of methanol and water (90:10 v/v) adjusted to pH 8.90 with a phosphate buffer. The HPLC analysis was carried out at 25 °C column temperature with 1.0 mL/min isocratic flow rate of the mobile phase. The robustness of the method was evaluated changing the flow rate of the mobile phase (0.9 mL/min and 1.0 mL/min) and the column temperature (23 °C and 25 °C). Result: The mean recovery data for the ketoconazole pharmaceutical dosage forms were in the range of 92.67–105.23%. Conclusion: The developed and validated method was successfully used for the quantitative analysis of ketoconazole pharmaceutical dosage forms; tablets, topical cream, and shampoo.
Keywords: tablets